2021
DOI: 10.3390/foods10092154
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Ultrasound and Surfactants on Nanobubbles Efficacy against Listeria innocua and Escherichia coli O157:H7, in Cell Suspension and on Fresh Produce Surfaces

Abstract: Removing foodborne pathogens from food surfaces and inactivating them in wash water are critical steps for reducing the number of foodborne illnesses. In this study we evaluated the impact of surfactants on enhancing nanobubbles’ efficacy on Escherichia coli O157:H7, and Listeria innocua removal from spinach leaves. We evaluated the synergistic impact of nanobubbles and ultrasound on these two pathogens inactivation in the cell suspension. The results indicated that nanobubbles or ultrasound alone could not si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This characteristic is particularly valuable for applications that require stringent environmental compliance [129]. This makes them especially suited for applications such as water treatment and sensitive bioprocesses, where chemical changes can adversely affect microbial communities [136]. Their prolonged presence and ability to improve gas availability mean that fewer external inputs are required, contributing to resource conservation and minimizing environmental impacts.…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic is particularly valuable for applications that require stringent environmental compliance [129]. This makes them especially suited for applications such as water treatment and sensitive bioprocesses, where chemical changes can adversely affect microbial communities [136]. Their prolonged presence and ability to improve gas availability mean that fewer external inputs are required, contributing to resource conservation and minimizing environmental impacts.…”
Section: Discussionmentioning
confidence: 99%
“…A synergistic study combining pure O 2 ‐nanobubble solution followed by ultrasonication for 5–20 min against an initial count of 6–7 log CFU mL −1 E. coli O157:H7 and L. innocua on spinach leaves was performed; the treatment resulted in >6 log CFU mL −1 reduction of L. innocua after 15 min and 7 log CFU mL −1 reduction for E. coli after 10 min. Nanobubbles in combination with ultrasonication also improved bacterial removal from the surface of spinach leaves, eliminating >2 and 4 log CFU cm −2 of L. innocua and E. coli , respectively (Rafeeq & Ovissipour, 2021). Le Nguyen et al.…”
Section: Impact Of Activated Water Systems On Spoilage and Microbial ...mentioning
confidence: 99%
“…However, extreme internal pressure, temperature, and a rapid collapse are required to support adiabatic compression during MNB collapse to produce ROS. One of the most important ROS generated by oxygen and air MNB is hydroxyl radicals (Rafeeq & Ovissipour, 2021). However, it is still unknown whether MNB‐derived hydroxyl radicals can be produced without applying mechanical and ultrasonic agitation or by lowering pH of the solution (Takahashi et al., 2021; Yasui et al., 2018).…”
Section: Chemical Pathways Of Activated Water Systemsmentioning
confidence: 99%
“…Several studies have demonstrated the potential of power ultrasound alone or combined with antimicrobial compounds such as chorine, PAA, or organic acids to reduce the bacteria load on the fresh produce surfaces [13,[16][17][18][19][20]. However, many of the studies evaluated washing conditions that were not practical for industry use (e.g., long treatment times).…”
Section: Introductionmentioning
confidence: 99%